Apakah Pemasaran Media Sosial, Pemasaran Influencer, dan Strategi Respons Berpengaruh terhadap Penjualan Coffee Shop X? - Monica Farissa Zain; Rayhan Gunaningrat; Esti Dwi Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine whether social media marketing, influencer marketing, and customer response strategies affect actual sales at Coffee Shop X in Surakarta. The research background is based on the growing use of digital marketing strategies in the food and beverage industry, while their effectiveness in boosting sales remains to be proven. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4, supported by normality testing via SPSS. Primary data were collected through an online questionnaire distributed to 100 active customers of Coffee Shop X, while secondary data consisted of actual sales records over 100 days. The results show that all three independent variables have a positive and significant effect on sales, both partially and simultaneously. The coefficient of determination (R²) of 0.147 indicates that the independent variables explain 14.7% of sales variation, while the Q² value of 0.015 suggests low yet relevant predictive ability. These findings imply that coffee shop businesses should optimize digital marketing strategies, strengthen collaborations with relevant influencer s, and improve customer response speed to enhance sales.